1990
DOI: 10.1200/jco.1990.8.10.1707
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for myelodysplasia and secondary acute nonlymphoblastic leukemia.

Abstract: Twenty-three patients with primary myelodysplasia (MDS) or secondary myelodysplasia/acute nonlymphocytic leukemia (MDS/ANLL) were treated with allogeneic or syngeneic bone marrow transplantation (BMT). Only one patient was in a chemotherapy-induced hematologic remission. Graft-versus-host disease prophylaxis included methotrexate, methotrexate plus cyclosporine, cyclosporine, or T-cell depletion using one of two anti-CD5 monoclonal antibodies. For patients with primary MDS, the median age was 19 years (range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 20 publications
5
27
0
2
Order By: Relevance
“…Meanwhile, the outcome of allogeneic BMT for sAML was also reported to be worse than that for de novo AML. 23,24 Prolonged disease-free survival can be expected in only about 20% of patients transplanted for sAML. 25 Anderson et al 26 also reported that the 5-year survival of secondary AML patients was 24.4% after stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the outcome of allogeneic BMT for sAML was also reported to be worse than that for de novo AML. 23,24 Prolonged disease-free survival can be expected in only about 20% of patients transplanted for sAML. 25 Anderson et al 26 also reported that the 5-year survival of secondary AML patients was 24.4% after stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Actuarial diseasefree survival (DFS) ranges between 35 and 45% at 2 to 4 years after BMT. [4][5][6][7][8] About 30% of younger patients with MDS/sAML will have an HLA-identical sibling donor and about 5% a one HLA locus mismatched family donor. Increasing size of the voluntary unrelated donor registries facilitates the identification of matched unrelated donors for about 75% of patients.…”
mentioning
confidence: 99%
“…Disease-free survival ranges from 29 to 40% with a corresponding nonrelapse mortality of 37-50% and a rate of relapse ranging from 23-48% if the donor is an HLA-identical sibling. [1][2][3] If unrelated donors were used, after standard myeloablative conditioning the treatmentrelated mortality exceeded more than 50%. 4 Despite an improvement in the results of allogeneic stem cell transplantation during the past decade mainly due to a lower treatment-related mortality, there is still a high morbidity, which makes allogeneic stem cell transplantation after standard conditioning only appropriate for younger patients with good performance status.…”
Section: Introductionmentioning
confidence: 99%